A fatal glow - Wesley, Valerie Wilson (Wesley, Valerie Wilson. Odessa Jones mystery, 2022)
"Recently widowed Odessa Jones is sure the exclusive catering job she's scored from wealthy businessman Casey Osborne will propel her catering career into the big leagues. So when Dessa's pesky second sight warns her that Osborne is bad news, she ignores it. She wishes she hadn't when he drops dead at his brunch after sampling her homemade preserves. Osborne's death is declared a homicide. Dessa and the friends who helped her cook are considered suspects... To clear her name and find the truth, Dessa delves into Casey Osborne's life. Everyone from his sinister business partner to his tormented ex-wife has reason to kill him--and the opportunity to do it. With the help of her spirited aunt, loyal co-workers and mischievous cat Juniper, she desperately searches for answers. Until a second murder leads Dessa down a frightening path filled with insidious hidden agendas--and someone poised to change her life forever" -- Back cover.